IMPLEMENTATION OF DATA MINING ALGORITHM FP-GROWTH IN MILK SALES IN PT. ASIA JAYA TOGETHER USING ASSOCIATION RULE METHOD - Tajrin, Tajrin; Samosir, Samuel; Aritonang, Lilis Suryani (Sean Institute, 2022)
This study aims to determine the types of dairy products that are most often sold based on weekly sales data. In addition, this study aims to find out what type of milk will be in more stock, and to place milk in one cupboard with several types of milk that are often purchased by consumers. With this aim for time efficiency in making it easier for consumers to take goods, and make the company easier for sure. This research was conducted at PT. Asia Jaya Bersama, Medan City, North Sumatra. The basic method used in this research is the association rule method and its implementation uses the survey method. The algorithm used to simplify the method is the frequent pattern growth (fp-growth) algorithm